2019
DOI: 10.1186/s12866-019-1401-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of multidrug-resistant ST2 Acinetobacter baumannii isolated from Saint George hospital in Lebanon

Abstract: BackgroundAcinetobacter baumannii is an opportunistic pathogen causing various nosocomial infections. The spread of multidrug-resistant A. baumannii is a major public health problem. The aim of this study was to investigate the molecular epidemiology and the genetic support of multidrug-resistant A. baumannii isolates collected from Saint-Georges Hospital in Lebanon.MethodsBetween January and August 2016, 31 A. baumannii isolates were collected from sputum samples of patients infected with ventilator-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…However, none of this study's isolates had STs similar to those of Indian and Iranian isolates. In Asia, ST2 has been described as the most prevalent sequence type among CRAB in China and Lebanon [28,35]. ST2 belongs to CC2 in the Pasteur scheme and corresponds to CC92 in the Oxford scheme and international clone II, as previously identified [36].…”
Section: Discussionmentioning
confidence: 73%
“…However, none of this study's isolates had STs similar to those of Indian and Iranian isolates. In Asia, ST2 has been described as the most prevalent sequence type among CRAB in China and Lebanon [28,35]. ST2 belongs to CC2 in the Pasteur scheme and corresponds to CC92 in the Oxford scheme and international clone II, as previously identified [36].…”
Section: Discussionmentioning
confidence: 73%
“…Our previous work demonstrated that most carbapenem-resistant Acinetobacter baumannii isolates (CRAB) in Thailand were ST2 clones, but some belonged to ST25, ST98, ST129, ST164, ST215, ST338, and ST745 [ 26 ]. In Asia, ST2 has been reported as the most prevalent sequence type of CRAB in China and Lebanon [ 24 , 43 , 44 ]. Sequence typing of A. baumannii distributed in Thailand was conducted in a study of 23 samples from a single hospital setting using the Oxford MLST scheme [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“… 41 , 42 A Lebanon study reported the detection of ST2 A. baumannii harboring NDM-1. 43 Several studies from Pakistan have described the detection of A. baumannii ST2 clones. 29 , 39 ST2 (CC2) can survive in the clinical settings for longer times, allowing for the acquisition of AMR genes, which can complicate treatment.…”
Section: Discussionmentioning
confidence: 99%